Research of level of psychological preparedness of 30–40 years old tourists skiers in the preparation period - Топорков Олександр Миколайович, (Alexander Toporkov) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: сompare the results of research of the psychological state of 30–40 years old tourists skiers at various stages of preparation period. Material and Methods: 14 people aged 30 to 40 years old who have a different experience in water, hiking and mountain as well as ski-sport hiking took part in research. Analysis of scientific and methodical literature, pedagogical observations, pedagogical experiment, methods of mathematical statistics is used. Results: the test results of 30–40 years old tourists skiers which are the participants in the experimental group received at different stages of preparation period and the results. Their comparative analysis is held. Conclusions: it was found that, at the stages of preparation period indicators of personal qualities and concentration had always risen, reaching the highest degree at the end of the experiment.